2009
DOI: 10.1007/s00134-009-1426-3
|View full text |Cite
|
Sign up to set email alerts
|

Hypercapnia in late-phase ALI/ARDS: providing spontaneous breathing using pumpless extracorporeal lung assist

Abstract: Elimination of CO(2) by p-ECLA therapy allowed reduction of ventilator-induced shear stress through ventilation with tidal volumes below 4 ml/kg predicted body weight in pneumonia patients with severely impaired pulmonary compliance during late-phase ARDS. p-ECLA treatment supported control of breathing pattern while sedation requirements were reduced and facilitated the implementation of assisted spontaneous breathing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 27 publications
0
18
0
1
Order By: Relevance
“…In total, 14 studies were included: two RCTs (Table 1) [18,19], and six prospective observational studies [20-25] and six retrospective studies [26-31] (Table 2). The earliest study dated from 1986 and the most recent from 2013.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 14 studies were included: two RCTs (Table 1) [18,19], and six prospective observational studies [20-25] and six retrospective studies [26-31] (Table 2). The earliest study dated from 1986 and the most recent from 2013.…”
Section: Reviewmentioning
confidence: 99%
“…Five studies (two RCTs and three retrospective studies) reported ICU length of stay [18,19,26,27,29]. Neither RCT demonstrated a significant reduction in ICU length of stay.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Pumpless arteriovenous extracorporeal lung assist (pECLA) is used increasingly in trauma patients. 14,15 The highly effective CO 2 elimination via pECLA allows separation of ventilation from oxygenation. The required mean airway pressure as the main determinant for oxygenation can be maintained with a respiratory pressure amplitude that is significantly reduced, especially if pE-CLA is combined with HFOV.…”
mentioning
confidence: 99%
“…Bisher wurden die Verfahren fast ausschließlich bei ARDS-Patienten unter kontrollierter Beatmung verwendet. In einzelnen Fallserien konnte gezeigt werden, dass die Verfahren auch an wachen Patienten effektiv sind und über die Elimination des CO 2 die Atemlast der Patienten reduziert und der Anteil der Spontanatmung verbessert[154] werden. Aktuell werden neuere veno-venöse Systeme mit kleineren Pumpen entwickelt, die trotz geringerer Flussraten effektiv CO2 auswaschen.…”
unclassified